Perancangan Interior Galeri Batik Semar di Surabaya - Lintu Tulistyantoro, Maria Adelia Nugroho (Intra, 2014)
Batik is Indonesiaâs most famous culture product, well known by both local community and international society. Unfortunately the art of batik nowadays is abandoned and underestimated by Indonesians themselves especially by the youngsters because batik has been regarded old and out of date. One of the ways to attract peopleâs interest in batik is creating a place, in this case is a shop or batik gallery with modern but featuring Indonesia cultures element as well, therefore it fascinates the visitors to come for admiring and even purchasing the batik products.In the interior design of Batik Semar Gallery in Surabaya, there are facilities such as retail shop of Batik Semar batik cloth, apparel, and accessories or souvenir and workshop space of batik cloth processing purposely shown to the visitors where they can watch and even take part in producing the batik. Dynamic is used as a concept, applied in shapes, lines, and layout composition in this design. It is expected that this design can raise the value of PT Batik Semarâs products.